Five Year Survival of Active Multiple Myeloma Patients Based on Durie-Salmon and International Myeloma Working Group 2003 Diagnostic Criteria - Kurniawati, Sri Agustini; Reksodiputro, Ary Harryanto; Atmakusuma, Tubagus Djumhana (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. Survival of active multiple myeloma (MM) patients is determined by early diagnosis and various prognostic factors. The development of MM diagnostic criteria from Durie-Salmon (DS) criteria to International Myeloma Working Group (IMWG) 2003 is an attempt to diagnose active MM earlier. However, due to limited resources, these diagnostic criteria cannot be fulfilled consistently in Indonesia. Based on this reason, it is necessary to know the proportion of MM based on DS and IMWG 2003 diagnostic criteria and also their impact on the survival of MM patients in Indonesia. Methods. This was a retrospective cohort study with survival analysis. Subjects were active MM patients in Cipto Mangunkusumo Hospital and Dharmais Cancer Hospital during 2005-2015. Data were presented in Kaplan-Meier survival curve and table with 95% confidence interval (CI). Results. This study involved 102 active MM patients with complete diagnostic data and survival for more than 1 month. As much as 56.9% of patients met DS diagnostic criteria and 72.5% met IMWG 2003 criteria. Median of overall survival (OS) based on DS criteria (77.8 months) was similar with IMWG 2003 criteria. Overall survival in the first, third, and fifth year of MM patients who met DS criteria were 89.9%, 77.5%, and 54.8%, respectively. Meanwhile overall survival in the first, third, and fifth year of MM patients who met IMWG 2003 criteria were 87.5%, 75.6% and 55.9%, respectively. Conclusions. The proportion of active MM patients who met IMWG 2003 diagnostic criteria was higher than those who met DS criteria. Overall survival of active MM patients who meet DS diagnostic criteria is similar with those who met IMWG 2003 criteria.